Unraveling the complexity of the organic food market: Indonesian consumer perspective on price and product knowledge - Luthfiana, Della Nanda; Andika, Andika; Bidayati, Utik (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2024)
In the past decade, the organic food industry has witnessed a tremendous surge in popularity as consumers increasingly perceive it as a healthier, more natural, and more environmentally friendly alternative to conventional foods. This trend has prompted extensive research into consumer behavior towards organic food, mainly focusing on the factors that drive its acceptance. Despite its growing interest, the adoption of organic food faces considerable challenges, mainly due to its higher price. This study examines Indonesian consumers’ willingness to pay more for organic food (WTPM) by examining the role of product knowledge (PK), consumer attitude (CA), and price consciousness (PC). Data was collected from 250 respondents representing consumers in Indonesia through an online survey. Descriptive Statistical Analysis and Structural Equation Modeling (SEM) are used to test hypotheses and understand relationships between variables. The results show that PK significantly affects CA towards organic food but does not directly affect WTPM. In addition, CA emerged as a significant mediator between PK and WTPM, indicating that consumers with positive CA towards organic food tend to pay more, as they see the cost as an investment for environmental sustainability and health. However, this relationship is moderated by PC, which indicates that price sensitivity may reduce the effect of positive CA on WTPM. The findings of this study underscore the need for a multifaceted approach to promoting organic food. To increase consumer acceptance and uptake, strategies should include education initiatives, awareness raising, and addressing issues related to price and perceived value.